Current Updates on Interventional Cardiac Electrophysiology - Liu, Tong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Rapid developments have taken place over the recent years in the interventional cardiac electrophysiology. New methods and tools in the diagnosis and treatment of cardiac arrhythmia have emerged. There are many questions which still present a challenge, such as the ablation of refractory ventricular tachycardia, how to improve the long-term success rate of persistent atrial fibrillation, the long-term effectiveness and safety of His-Purkinje conduction system pacing. Accordingly, we dedicate this Special Issue Current Updates on Interventional Cardiac Electrophysiology to gathering the most recent progress in this field. Its aim is to present an overview of the current knowledge, latest evidence, and unresolved issues in this field. More specifically, the topics of interest include but are not limited to: atrial fibrillation; cryoablation; radiofrequency ablation; cardiac resynchronization therapy; His-Purkinje conduction system pacing; stereotactic radiotherapy for refractory ventricular tachycardia; pulsed electric field ablation; leadless pacemakers; and implantable cardioverter-defibrillators.